Amazonia trees have limited capacity to acclimate plant hydraulic properties in response to long‐term drought. (30th March 2020) - Bittencourt, Paulo R. L.; Oliveira, Rafael S.; da Costa, Antonio C. L.; Giles, Andre L.; Coughlin, Ingrid; Costa, Patricia B.; Bartholomew, David C.; Ferreira, Leandro V.; Vasconcelos, Steel S.; Barros, Fernanda V.; Junior, Joao A. S.; Oliveira, Alex A. R.; et al.
Abstract: The fate of tropical forests under future climate change is dependent on the capacity of their trees to adjust to drier conditions. The capacity of trees to withstand drought is likely to be determined by traits associated with their hydraulic systems. However, data on whether tropical trees can adjust hydraulic traits when experiencing drought remain rare. We measured plant hydraulic traits (e.g. hydraulic conductivity and embolism resistance) and plant hydraulic system status (e.g. leaf water potential, native embolism and safety margin) on >150 trees from 12 genera (36 species) and spanning a stem size range from 14 to 68 cm diameter at breast height at the world's only long‐running tropical forest drought experiment. Hydraulic traits showed no adjustment following 15 years of experimentally imposed moisture deficit. This failure to adjust resulted in these drought‐stressed trees experiencing significantly lower leaf water potentials, and higher, but variable, levels of native embolism in the branches. This result suggests that hydraulic damage caused by elevated levels of embolism is likely to be one of the key drivers of drought‐induced mortality following long‐term soil moisture deficit. We demonstrate that some hydraulic traits changed with tree size, however, the direction and magnitude of the change was controlled by taxonomic identity. Our results suggest that Amazonian trees, both small and large, have limited capacity to acclimate their hydraulic systems to future droughts, potentially making them more at risk of drought‐induced mortality. Abstract : The fate of tropical forests under future climate change is dependent on the capacity of their trees to adjust to drier conditions. Following 15 years of experimentally imposed moisture deficit, Amazon trees showed no adjustment in their hydraulic traits to moisture deficit. This failure to adjust resulted in these drought‐stressed trees experiencing significantly reduced water potential and increased hydraulic failure. Both, small and large trees equally, could not adapt to moisture deficit. Our results suggest Amazon trees have a limited capacity to adjust to future droughts.